Alliance size and airline performance / Robert T. Hamilton and Sussie C. Morrish (Faculty of Business and Management ; UiTM Press, 2005)
This paper is a replication and extension of some previous work that seeks to isolate the effect of alliance size on the profitability of nine international airlines over the period from 1985 through to 2000. The paper begins with two contrasting industry viewpoints on the effect of alliances on airline performance. The findings suggest that, while the number of alliance partners has some effect in raising employee productivity, it has no direct effects on the passenger loadings or pricing behaviour Furthermore, we found no evidence that alliance size has any direct effect on the overall profitability of the airlines involved and, in particular, none to suggest that larger alliances lead to higher airfares. We conclude that it is higher employee productivity and the ability of a carrier to charge higher fares per passenger per kilometre that are the main influences on airline profitability.